Severe Hypertriglyceridemia in a Child with Refractory, Fatal Diabetic Ketoacidosis: A Case Report with Review of Literature - Shyna Soin; Gurmeet Kaur; Varun Kaul; Dorthy Batra (Wolters Kluwer Medknow Publications, 2024)
Background: Diabetic ketoacidosis (DKA) is an acute life-threatening complication of diabetes. Dyslipidemia due to disturbance in glucose metabolism can cause elevation in serum triglyceride levels. Severe hypertriglyceridemia is a complication of DKA, rarely reported in children. Clinical Description: A 3-year-old girl, newly diagnosed, but untreated type 1 diabetes mellitus (DM), presented with DKA. The first blood sample showed serum as grossly milky, with highly raised levels of triglyceride (2170 mg/dL) and cholesterol (791 mg/dL). Many of the blood parameters were erroneous due to the lipemic sample. Serum amylase and lipase were normal, ruling out pancreatitis. Management and Outcome: Correction of dehydration, insulin infusion, antibiotics, and vasopressor support were started. Despite treatment with insulin and supportive care, the patient had a rapidly deteriorating course and ultimately succumbed to the illness. Conclusion: Uncontrolled, untreated DM in a child can result in decompensated DKA, which is usually associated with severe hypertriglyceridemia, and a rapidly progressive fatal course.